Bioidentical, Synthetic, and Animal Based Hormone Replacement Therapies and Risk of Breast Cancer [1M]. (May 2017) - Abenhaim, Haim Arie; Czuzoj-Shulman, Nicholas; Spence, Andrea R.; Azoulay, Laurent; Suissa, Samy; Tulandi, Togas
Abstract : INTRODUCTION: Hormone Replacement Therapy (HRT) has been associated with an increased risk of breast cancer. Our study objective was to evaluate whether the increased risk is dependent on the formulation used. METHODS: We carried out a population-based case-control study using data from the United Kingdom Clinical Practice Research Datalink on women aged >50. Newly diagnosed breast cancer cases were age-matched with women of comparable follow-up time with no history of breast cancer at a 1:10 ratio. Exposures were classified as ever/never for the HRT formulations: Bioidentical Estrogens (BE), Conjugated Equine Estrogens (CEE), Micronized Progesterone (MP), and Synthetic Progestogens (SP). Logistic regression estimated adjusted effects of HRT formulation on breast cancer. RESULTS: Between 1995-2014, 43, 183 cases of breast cancer were identified and matched to 431, 830 controls. Compared with women who had never used HRT, HRT use was associated with an overall increased risk of breast cancer OR 1.12 (1.09-1.15), p < 0.0001. Compared to never users, estrogens were not associated with breast cancer: BE (OR 1.04 (1.00-1.09), p=0.07), CEE (OR 1.01 (0.96-1.05), p=0.78), both (OR 1.32 (0.30-5.77), p=0.25). As compared to never users, progestogens appeared differentially associated with breast cancer: MP (OR 0.99 (0.55-1.79), p=0.98), SP (OR 1.28 (1.22-1.35), p < 0.0001), both (OR 1.32 (0.30-5.77), p=0.72). CONCLUSION: While HRT use is associated with an overall increased risk of breast cancer, this association appears to be uniquely in women having been given synthetic progestogens. Synthetic progestogens should not be given as part of HRT and counseling regarding the risk of breast cancer should consider the effect of formulation used.